2015
DOI: 10.1038/srep11711
|View full text |Cite
|
Sign up to set email alerts
|

Whole genome amplification with SurePlex results in better copy number alteration detection using sequencing data compared to the MALBAC method

Abstract: Current whole genome amplification (WGA) methods lead to amplification bias resulting in over- and under-represented regions in the genome. Nevertheless, certain WGA methods, such as SurePlex and subsequent arrayCGH analysis, make it possible to detect copy number alterations (CNAs) at a 10 Mb resolution. A more uniform WGA combined with massive parallel sequencing (MPS), however, could allow detection at higher resolution and lower cost. Recently, MALBAC, a new WGA method, claims unparalleled performance. Her… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
53
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(56 citation statements)
references
References 21 publications
2
53
0
Order By: Relevance
“…The variance of the read counts per window across the genome for the current TruePrime samples is a lot higher compared to the variance in the previously analyzed SurePlex samples3 (p = 0.015; Fig. 4).…”
Section: Resultsmentioning
confidence: 60%
See 2 more Smart Citations
“…The variance of the read counts per window across the genome for the current TruePrime samples is a lot higher compared to the variance in the previously analyzed SurePlex samples3 (p = 0.015; Fig. 4).…”
Section: Resultsmentioning
confidence: 60%
“…The setup of this study was equal to the SurePlex study3, except for the WGA method used. The same cell line and cell isolation techniques were used.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, an improved ability of MALBAC in SNP variant identification has been recently reported, with better performance in uniformity and reproducibility [48]. Other methods, like SurePlex allows for a better copy number alterations (CNAs) detection, with a more uniformity amplification across the genome [49]. These observations led us to endorse MALBAC as the technique to be used in genotyping the ESR1 gene.…”
Section: Discussionmentioning
confidence: 99%
“…Probably due to the amplification bias introduced by the WGA protocol more sequencing is needed to obtain a similar resolution (21). Although several new WGA methods have been described, we and other investigators have shown that the SurePlex method used in the present study introduces the least amplification bias (22). Although MPS is a technique that allows scaling, the WGA is currently the limiting factor in achieving higher resolution copy number profiles when starting from a single or a limited number of cells.…”
Section: Discussionmentioning
confidence: 91%